Pengembangan Booklet Jenis Echinodermata Berbasis Potensi Lokal Pantai Pandaratan untuk Meningkatkan HOTS Siswa Kelas X SMA: Development of a Local Potential-Based Echinoderm Booklet from Pandaratan Beach to Enhance the Higher-Order Thinking Skills of Grade 10 Senior High School Students - Putri Nora; Martina Restuati; Syahmi Edi (Al-Musannif, 2026)
Students' Higher-Order Thinking Skills (HOTS) remain relatively low, while the utilization of local potential as a biology learning resource is still limited. This study aimed to develop an Echinoderm diversity booklet based on the local potential of Pandaratan Beach and examine its effectiveness in enhancing students' HOTS. The study employed the 4D Research and Development model consisting of Define, Design, Develop, and Disseminate stages. Data were collected using validation sheets, response questionnaires, and HOTS tests. The booklet was rated highly feasible by material experts (92.96%), instructional design experts (94.31%), and graphic design experts (86.02%). Teacher and student responses were highly positive, with scores of 99.00% and 97.04%, respectively. The experimental class obtained a higher posttest mean score (83.80) than the control class (73.95), with N-Gain values of 0.74 (high category) and 0.59 (moderate category), respectively. An independent samples t-test revealed a significant difference between the two groups (p < 0.05). These findings indicate that the booklet is both feasible and effective in improving students' HOTS. Therefore, the booklet can serve as an alternative local potential-based learning resource to support contextual biology learning in senior high schools.